The structural contingency model of trust: When variability in perceived trustworthiness of scientists signals critical support - Tenzin Tamang (Public Understanding of Science, 2026)
Prevailing approaches to measuring public trust in scientists rely on facet averages that overlook within-person variability, a dimension traditional views equate with ambivalence or attitudinal weakness. This study introduces the Structural Contingency Model of Trust (SCMT), proposing that the functional meaning of this variability is contingent on an individual’s overall trust level. In a Bayesian analysis of survey data from 68 countries ( N = 69,534), higher Trust Level (mean across 12 facets) strongly predicted greater general confidence in scientists. Critically, a credible interaction effect supported the SCMT: among highly trusting individuals, greater Trust Variability (variance across facets) was associated with the highest probability of reporting a great deal of confidence in scientists. This Critical Support profile suggests that variability can signify robust, differentiated engagement rather than evaluative weakness, offering a nuanced framework for understanding the complex, multidimensional nature of public trust in scientists.